EXISTENCE OF PERIODIC SOLUTIONS FOR A CLASS OF NEUTRAL DIFFERENTIAL EQUATIONS WITH IMPULSES - Afonso, Suzete M. [UNESP]; Furtado, Andre L. (Rocky Mt Math Consortium, 2020)
By applying a Mawhin continuation theorem of coincidence degree theory, we establish sufficient conditions for the existence of a periodic solution for a class of impulsive neutral differential equations. The procedure adopted in this work makes use of a nonimpulsive associated equation in order to overcome the difficulties resulting from the moments of impulse effects.
Keywords: impulsive neutral differential equations; coincidence degree; continuation theorems